If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 22 = 90 Reorder the terms: 22 + 4t = 90 Solving 22 + 4t = 90 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 4t = 90 + -22 Combine like terms: 22 + -22 = 0 0 + 4t = 90 + -22 4t = 90 + -22 Combine like terms: 90 + -22 = 68 4t = 68 Divide each side by '4'. t = 17 Simplifying t = 17
| 3z+2=(z-3)+9 | | (x-3)(-15)= | | 9m-3(2m-3)=11 | | -(67r+67s-94)= | | 2x+8=-24 | | 5+14-2w=9-(4w+2) | | 45+0.20m=66 | | 11x-4=56-x | | 25.24=5x+3.89 | | 4(x+15)=60 | | 2x-(3y+4z)= | | 117=-39x | | 12n+4-5n=42 | | 2z^2-9z-5=0 | | 42.55+0.20m=90 | | 4w-1=5w+37 | | -8=3(-x+2)-x | | 16+5a=13a | | 1-2r=8-3r | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^3)=0 | | x^2+0.4x-0.3=0 | | 12n-(14m-8m)= | | 3-2y=15+14y | | 8n-(n+3)=9 | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^2)=0 | | 5x-5+7x=17 | | 3x+2(x-6)=3 | | 96=600(.04)t | | -3x+=-54 | | 8+p=2p+3 | | X=log-25 | | 0.4x+0.7(x-3)= |